Analisis Pembelajaran IPA Pada Materi Cahaya di SD 2 HKBP Sidorame - Bintang Adriani Hutasoit; Suyit Ratno; Lyra Kartika; Alya Zulfa Ramadhani; Driana Stefani Tambunan; Luthfi Vivia Diwani; Siti Hawaliah Hasibuan (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to determine the increase in students' knowledge through learning based on analytical and innovative models in understanding light material. The method used in this study is the analytical research method. This study is a classroom action research conducted on fifth grade elementary school students. The research sample consisted of 13 students. Data collection was carried out through written test techniques given to students before and after the application of the learning model. The data obtained were analyzed using techniques to see the analysis of the increase in students' understanding of light material. The results of the data analysis showed that there were still many students who did not understand the concept of light well, especially in terms of the properties of light and its application in everyday life. Therefore, it is necessary to apply more interactive and innovative learning methods so that students can more easily understand the material. This study recommends the use of more varied learning strategies to optimally improve student understanding.